A discourse analysis of young adults' discussions of intimate partner violence in dating relationships - Barkhuizen, Lauren Ruth (Department of Psychology, 2014)
Research on intimate partner violence (IPV) has focused predominantly on the married or cohabiting adult population in South Africa;; however, IPV also occurs in young adults' dating relationships. The purpose of this research was to explore the discourses young adults at a South African university collectively drew upon in peer-group discussions on the topic of IPV in dating relationships. Six focus groups were conducted with a total of 31 students between the ages of 18 and 26 who were recruited through the distribution of flyers and posters advertising the study at the University of Cape Town (UCT). Foucauldian discourse analysis was used to identify 3 main discourses in participants' talk on IPV in dating relationships, namely the discourse of 'othering', the discourse of men's authority, and the discourse of women's responsibility. Related sub-discourses were also unearthed, which included the discourse of women as abusive, the discourse of men's sexual entitlement, explanatory discourses on IPV, and the discourse of love and violence. The identified discourses enabled students to simultaneously obfuscate and demonstrate the existence of IPV in the UCT context;; - to talk about IPV as a normal, acceptable and inevitable part of men's authoritative and sexually entitled behaviour in dating relationships and to talk about IPV as women's responsibility bound by constructions of love. Overall, this study has shown how dominant discourses of IPV and gender power inequity amongst young adults might encourage male violence and dominance, and women's victimisation and passivity.